Synthesis of methyl-protected (+/-)-chlorizidine A - Mahajan, Jyoti P.; Mhaske, Santosh B. (Organic Letters, 2017)
The first total synthesis of the methyl-protected (+/-)-chlorizidine A has been achieved in 10 steps. Pd-catalyzed decarboxylative coupling and late-stage oxidation were utilized to, construct the 5H-pyrrolo[2,1-a]isoindol-5-one scaffold. Samarium(II) iodide mediated Reformatsky reaction and intramolecular Mitsunobu reactions were efficiently applied for the synthesis of the 2,3-dihydropyrrolizine ring system. Chlorizidine A is highly prone to degradation; hence, methyl-protected (+/-)-chlorizidine A was prepared.